Proceedings ITCC 2003. International Conference on Information Technology: Coding and Computing
DOI: 10.1109/itcc.2003.1197507
|View full text |Cite
|
Sign up to set email alerts
|

A learning objects approach to teaching programming

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Some researchers stated that using animations gives an exact and rich representation for some topics that are very hard to comprehend from text-based information (Falvo, 2008;Rotbain, Marbach, & Stavy, 2008). Several researchers concluded that the use of learning objects contributes significantly to the teaching-learning process of programming (Adamchik & Gunawardena, 2003;Begosso, Begosso, L., Begosso, Ribeiro, & Martins, 2015;Narasimhamurthy & Shawkani, 2009). Halverson, Wolfenstein, Williams, and Rockman (2009) described how the design of digital learning objects can spark professional learning.…”
Section: Litreture Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers stated that using animations gives an exact and rich representation for some topics that are very hard to comprehend from text-based information (Falvo, 2008;Rotbain, Marbach, & Stavy, 2008). Several researchers concluded that the use of learning objects contributes significantly to the teaching-learning process of programming (Adamchik & Gunawardena, 2003;Begosso, Begosso, L., Begosso, Ribeiro, & Martins, 2015;Narasimhamurthy & Shawkani, 2009). Halverson, Wolfenstein, Williams, and Rockman (2009) described how the design of digital learning objects can spark professional learning.…”
Section: Litreture Reviewmentioning
confidence: 99%
“…The interactive learning objects are appreciated by many instructors in search of new methods and supports for novice programming students (Matthiasdottir, 2006). Several studies showed that the use of learning objects contributes significantly to the improvement of computer science teaching-learning process (Adamchik & Gunawardena, 2003;Andreza & Magalhães, 2019;Begosso et al, 2015;Cavus & Ibrahim, 2004; Jaimez-González, García-Mendoza, Luna-Ramírez, Nápoles-Duarte, & Vargas-Vargas, 2018; Luna-Ramírez & Jaimez-González, 2014; Narasimhamurthy & Shawkani, 2009;Tapoli & Mikropoulos, 2019;Villalobos & Jiménez, 2009).…”
Section: Litreture Reviewmentioning
confidence: 99%
“…In addition to changes in language selection and use of visual environments, other approaches tied into pedagogy of teaching programing concepts are being explored. The use of Learning Objects (LO) are increasingly being explored which involves the creation of many exploratory and full scale learning tools [1,9]. Many LOs include aspects of animation, annotation, examples and visualization as a modularized component, which can often be integrated or developed for use in a Learning Management system [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pukkhem and Vatanawood [14] establishes that learning objects can be educational components presented in any format. Gunawardena and Adamchik [15] defines a LO as an integrated module containing core text, code examples, review questions, supplementary material, and programming labs.…”
Section: Learning Objectsmentioning
confidence: 99%
“…In this day and age, a person's ability to create and consolidate the knowledge required to do so is more important than ever, rather than just accumulating knowledge. This allows the development of skills such as critical thinking, problem solving, decision-making and technological understanding [15].…”
Section: Learning Objectsmentioning
confidence: 99%